1936
DOI: 10.1063/1.1749816
|View full text |Cite
|
Sign up to set email alerts
|

The Absolute Rates of Reaction of Hydrogen with the Halogens

Abstract: In this paper we apply the statistical-mechanical method which has only recently been developed for reaction rates to three new groups of reactions. These are the reactions of I2, Cl and Br with the various kinds of hydrogen molecules. In the first type (I2+H2→2HI) symmetry properties enable one to divide the six internal modes of vibrations for the four coplanar atoms into three sets with one, two and three modes of vibration in each so that in obtaining the frequency nothing greater than a cubic is solved. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1937
1937
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The stretching and bending frequencies in the activated complex are low [l 1, 231, whereas the present values, which are similar to Eyring's results [24], are considerably higher, therefore requiring a higher tunneling correction. I n addition to the possible sources of error in the present surfaces discussed above, Klein [25] has suggested that the overlap integral between the end atoms in 1H-2H-Cl might differ considerably from the integral for the two adjacent atoms (2H-C1 value for the diatomic halides based on the fact that they have similar molecular orbitals may not be strictly valid since the 5pn orbitals of H I may have appreciable bonding power [26].…”
Section: Discussionsupporting
confidence: 85%
“…The stretching and bending frequencies in the activated complex are low [l 1, 231, whereas the present values, which are similar to Eyring's results [24], are considerably higher, therefore requiring a higher tunneling correction. I n addition to the possible sources of error in the present surfaces discussed above, Klein [25] has suggested that the overlap integral between the end atoms in 1H-2H-Cl might differ considerably from the integral for the two adjacent atoms (2H-C1 value for the diatomic halides based on the fact that they have similar molecular orbitals may not be strictly valid since the 5pn orbitals of H I may have appreciable bonding power [26].…”
Section: Discussionsupporting
confidence: 85%
“…Valence bond theory has been used as a framework for modeling chemical reaction dynamics since the early days of quantum mechanics 2, 3, 20–24, 28, 29, 40, 41, 45, 48, 50, 51, 67, 72, 79, 81, 86, 87, 89, 90, 92, 95–99, 101–104, 106, 112, 210–286. In part this may be explained by the fact that valence bond theory often provides a concise description of multireference character, and transition states are more likely than stable molecules to exhibit multireference character.…”
Section: Potential Energy Surfacesmentioning
confidence: 99%
“…The method has proved to be a very efficient way to fit potential energy surfaces,312, 313 and it can be made even more efficient by using different amounts of data to interpolate different elements of the Hessian of the resonance integral314 and by adjusting the diagonal valence‐bond matrix elements as well as the off‐diagonal ones 320. Thus, the lessons learned from valence bond theory1–3, 13, 20–112, 210–286 can be imported into MCMM to provide improved representations of reactive potential energy surfaces.…”
Section: Potential Energy Surfacesmentioning
confidence: 99%
“…This was first applied by Eckert and Boudart (1963) to the bimolecular pyrolysis of hydrogen iodide. The model of Wheeler et al (1936) in equilibrium could be anticipated. Such effects are not unexpected, as dense gases can often have excellent solvent properties, interacting strongly with dilute species.…”
Section: Gas-phase Reactionsmentioning
confidence: 99%